Subtype distribution of lymphomas in Southwest China: Analysis of 6,382 cases using WHO classification in a single institution - Wang Xiao-Qing; Zuo Zhuo; Bi Cheng-Feng; Wang Wei-Ya; Xu Huan; Zhao Sha; Yu Jian-Bo; Zhang Wen-Yan; Yang Qun-Pei; Huang Juan; Dai Lin; Liu Wei-Ping (BMC, 2011)
Abstract Background The subtype distribution of lymphoid neoplasms in Southwest China was analyzed according to WHO classifications. This study aims to analyze subtype distribution of lymphomas in southwest China. Methods Lymphoid neoplasms diagnosed within 9 years in a single institution in Southwest China were analyzed according to the WHO classification. Results From January 2000 to December 2008, a total number of 6,382 patients with lymphoma were established, of which mature B-cell neoplasms accounted for 56%, mature T- and NK-cell neoplasms occupied 26%, and precursor lymphoid neoplasms and Hodgkin lymphomas were 5% and 13%, respectively. Mixed cellularity (76%) was the major subtype of classical Hodgkin lymphoma; and the bimodal age distribution was not observed. The top six subtypes of non-Hodgkin lymphoma were as follows: diffuse large B-cell lymphoma, extranodal NK/T-cell lymphoma, nasal type, extranodal marginal zone lymphoma of mucosa associated lymphoid tissue, follicular lymphoma, precursor lymphoid neoplasms, and chronic lymphocytic leukemia/small lymphocytic lymphoma. Extranodal lymphomas comprised about half of all cases, and most frequently involved Waldeyer's ring, gastrointestinal tract, sinonasal region and skin. Conclusions The lymphoid neoplasms of Southwest China displayed some epidemiologic features similar to those reported in literature from western and Asian countries, as well as other regions of China, whereas some subtypes showed distinct features. The high frequency of mature T/NK cell neoplasms and extranodal lymphomas, especially for extranodal NK/T-cell lymphoma, nasal type, is the most outstanding characteristic of this series.